Resilience and Vulnerability of Coastal Communities: A Case Study of Tambak Lorok, Semarang-Indonesia in Facing Flood Risks - Sammy Alidrus; Agus Wiyono (Jurnal Syntax Admiration, 2024)
This study examines the resilience and vulnerability of the Tambak Lorok coastal community in Semarang to recurring flood events. The research adopts a descriptive qualitative approach to explore the socio-economic, environmental, and infrastructural aspects influencing the community’s adaptive capacity. Through in-depth interviews, field observations, and document analysis, the study identifies key factors contributing to the community’s vulnerability, including reliance on flood-prone economic activities, inadequate housing infrastructure, and limited access to resources. The role of local institutions is also highlighted as a critical factor in enhancing community resilience through training and support programs. Despite ongoing mitigation efforts, such as the construction of levees and drainage improvements, the findings indicate that these measures have not fully protected the community from flood impacts. The study concludes with policy recommendations aimed at improving infrastructure, diversifying economic activities, and strengthening disaster mitigation strategies to enhance the long-term resilience of the Tambak Lorok community. This research contributes valuable insights into the challenges faced by coastal communities in adapting to the increasing risks posed by climate change and environmental hazards.